Análise de um modelo equivalente para um grupo de motores de indução trifásicos utilizados em simulações eletromecânicas - Rodrigues, Yuri Von Cosmy Bottoli (2019)
This work presents a methodology of aggregation of three-phase induction motors on a busbar, whether commercial or industrial, to reduce computational processing efforts in electrical system dynamics simulations. The mathematical formulation of such technique, based on the law of energy conservation, is also presented. The equivalent circuit parameters and moments of inertia of the various motors used in this research were cordially provided by WEG S.A. This was important to provide a solid basis for analyzing and comparing the performances of the group of motors with the equivalent aggregated motor by means of computer simulations of the electrical system under some disturbances. The results obtained graphically by electrical and mechanical variables confirmed the efficiency of the presented proposal.